Metal Ions Can Modulate the Self-Assembly and Activity of Catalytic Peptide Amyloids - Castillo-Nara, A; Diaz-Espinoza, R (American Chemical Society, 2024)
Rational design of peptides has become a powerful tool to produce self-assembled nanostructures with the ability to catalyze different chemical reactions, paving the way to develop minimalistic enzyme-like nanomaterials. Catalytic amyloid-like assemblies have emerged among the most versatile and active, but they often require additional factors for activity. Elucidating how these factors influence the structure and activity is key for the design. Here, we showed that biologically relevant metal ions can guide and modulate the self-assembly of a small peptide into diverse amyloid architectures. The morphology and catalytic activity of the resulting fibrils were tuned by the specific metal ion decorating the surface, whereas X-ray structural analysis of the amyloids showed ion-dependent shape sizes. Molecular dynamics simulations showed that the metals can strongly affect the local conformational space, which can trigger major rearrangements of the fibrils. Our results demonstrate that the conformational landscape of catalytic amyloids is broad and tunable by external factors, which can be critical for future design strategies. © 2024 American Chemical Society.